Pengaruh Kualitas Implementasi Metode Pembelajaran Ceramah Berbantuan Powerpoint dan Quizizz terhadap Hasil Belajar Kognitif dan Psikomotorik Mata Pelajaran Desain Grafis Percetakan di SMK Negeri 12 Malang - Rita Novi Dayanti; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The purposes of this study are: 1) to determine the influence of lecture method assisted by Quizizz on the cognitive learning outcomes of students, 2) to determine whether or not there is an effect on the implementation of the lecture method assisted by Quizizz on students' psychomotor learning outcomes, 3) to determine the influence of the quality of lecture method assisted by Quizizz media on the students' cognitive and psychomotor learning outcomes. The significance of this research is to provide information on how the influence and implementation of the lecture method assisted by Quizizz on students' learning outcomes. This research uses a semi-experimental method using a pseudo-experimental method (quasi-experiment). Experimental Research is a study that aims to determine the presence or absence of a cause and effect relationship through the treatment of the experiment group and the controls in comparison. Based on research conducted in SMK 12 Malang obtained the result that 1) there is an influence of the lecture method assisted by Quizizz media to the students ' cognitive learning outcomes, 2) the implementation of Quizizz on lecture method does not influence the students' psychomotor learning outcomes, 3) there is an influence on the quality of lecture method assisted by Quizizz to the students ' cognitive and psychomotor learning outcomes.